Zakat Paying Behavior and Gender Differences: The Case of Saudi Arabia - Hussein, Sarah Gamal; Osman, Ahmad Zamri (International Journal of Economics, Management and Accounting, 2022)
Zakat management is a significant mechanism for developing any Muslim country, both socially and economically. As zakat is an obligation for all Muslims, regardless of gender, and it is a tool for Muslim society socio-economic development, it is important to evaluate how zakat institutions can be sustained by assessing how different genders are perceiving zakat. Zakat plays a significant role in leveraging the productivity and efficiency of any Muslim society. It also plays a vital role in ensuring sustainable growth. This research investigates if there is any gender difference influencing the behavioral intention of zakat payment among Saudi men and women. The research used the Extended Theory of Planned Behavior (ETPB), which is an extension of the Theory of Reasoned Action (TRA) and Theory of Planned Behavior (TPB) to explore the factors affecting zakat payment behavior. This theory has six constructs that predict the intention to give zakat. Descriptive statistics and t-test were used to identify the difference in the variables across genders. The research summarized that gender differences occur in all ETPB factors, except for Perceived Behavioral Control (PBC). The results show that for the gender differences in the five variables, two variables of the theory of ETPB (Injunctive Norm and Past Behavior) are inclined toward women while another three variables (Attitude, Descriptive Norm, Moral Norm) are inclined toward men. Hence, the research can contribute to the policy making exercise in improving zakat administration in Saudi Arabia, especially in Jeddah.